2022
DOI: 10.1055/a-1847-5414
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Training Characteristics Between Junior, Under 23 and Professional Cyclists

Abstract: The aim was to compare the training characteristics of junior, under 23 and professional road cyclists. Training data collected during the 2019 competitive season of thirty male cyclists, divided into three age-related categories (JUN; U23; PRO), were retrospectively analyzed for training characteristics, external and internal training load. Higher duration per training session were observed in PRO (2.6 ± 0.3 h) compared to both U23 (2.2 ± 0.3 h; P < 0.001) and JUN (2.0 ± 0.2 h; P < 0.001). Elevation gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…However, whether the differences between the age-groups in the present study would have been more pronounced with a larger external energy expenditure remains speculative. Improved durability is possibly related to increased and consistent training loads over several years (42), also reflecting the increasing demands of cycling competitions from junior to U23 and senior levels (43). This is supported in a recent study that highlights a positive relationship between total training time spent at low intensities (i.e., below ventilatory threshold 1) and improvements in performance in the semifatigued state (29), which is in line with our general finding that the decrease in power from W max to 5-min test in a semifatigued state decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the differences between the age-groups in the present study would have been more pronounced with a larger external energy expenditure remains speculative. Improved durability is possibly related to increased and consistent training loads over several years (42), also reflecting the increasing demands of cycling competitions from junior to U23 and senior levels (43). This is supported in a recent study that highlights a positive relationship between total training time spent at low intensities (i.e., below ventilatory threshold 1) and improvements in performance in the semifatigued state (29), which is in line with our general finding that the decrease in power from W max to 5-min test in a semifatigued state decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…The eTRIMP use also was demonstrated in the comparison maximal oxygen consumption into athletes [5]. Besides that, eTRIMP has been used to compare the training characteristics of junior and professional athletes divided into age-related categories [6]. A prospective cohort study dose-response relationship between training load and anaerobic performance in female athletes suggested a curvilinear relationship the variance in changes of peak power output to eTRIMP method during a competition [7].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the preparation of three top-five cyclists for the Giro d’Italia [ 8 ], the training intensity distribution in world-class middle- and long-distance runners [ 12 ], and the training program of a world-class triathlete preparing for the Tokyo 2020 Olympic Games [ 9 ]. However, several studies have also been published using data from full seasons or prolonged training periods in elite junior and U23 athletes [ 11 , 13 , 14 , 15 ]. For example, Leo et al [ 11 ] observed how training characteristics varied across a competitive season and how they were related to the changes in the power profiles of elite U23 cyclists.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Leo et al [ 11 ] observed how training characteristics varied across a competitive season and how they were related to the changes in the power profiles of elite U23 cyclists. For their part, Gallo et al [ 14 ] compared training characteristics during the competitive season between junior, U23, and elite cyclists. These data can be of great interest because they can help coaches orient the training of athletes toward high performance in the elite category.…”
Section: Introductionmentioning
confidence: 99%